ABORSI KONTROVERSI DAN PILIHAN KEBIJAKAN - Muhadjir Darwin (Populasi, 1997)
Abortion is a controversial issue that had been a hot public debate in Indonesia after the Warakas tragedy. This article explores the ongoing debate between the so called pro-life and pro-choice groups, and formulate policy recommendations to overcome the abortion problem. The tough policyagainst the abortion would not solve the problem, rather it keeps the unsafe-abortion practised illegally and widely. The Government should be more realistic in dealing with this problem by providingearly abortion service at low cost so that women are protected from unsafe abortion.